2004
DOI: 10.1038/sj.onc.1207188
|View full text |Cite
|
Sign up to set email alerts
|

The MAP kinase pathway is required for entry into mitosis and cell survival

Abstract: In this communication, we examined the role of the MAP kinase pathway in the G2/M phase of the cell cycle. Activation of the Plk1 and MAP kinase pathways was initially evaluated in FT210 cells, which arrest at G2 phase at the restrictive temperature (391C), due to a mutation in the cdc2 gene. Previous studies had shown that these cells enter mitosis at the nonpermissive temperature upon incubation with okadaic acid, a protein phosphatase 1 and 2A inhibitor. We show that treatment of FT210 cells at 391C with ok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
109
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(124 citation statements)
references
References 49 publications
12
109
2
1
Order By: Relevance
“…Notably, the addition of rERK to shERK-transfected U251 and 5310 cells induced an obvious increase in the G 0 -G 1 peak. These results support previous findings by Liu et al [29] who demonstrated that inhibition of MEK1/2 in ERKdepleted cells arrest cells at the G 1 phase. This suggests that downregulation of ERK by hUCBSC may be regarded as a key step for the regulation of glioblastoma progression.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, the addition of rERK to shERK-transfected U251 and 5310 cells induced an obvious increase in the G 0 -G 1 peak. These results support previous findings by Liu et al [29] who demonstrated that inhibition of MEK1/2 in ERKdepleted cells arrest cells at the G 1 phase. This suggests that downregulation of ERK by hUCBSC may be regarded as a key step for the regulation of glioblastoma progression.…”
Section: Discussionsupporting
confidence: 93%
“…This model of competition is based on observations that inactivation of ERK1 by either genetic disruption or RNAi silencing increases the proliferation rate of fibroblasts, whereas knockdown of ERK2 expression dramatically inhibits cell proliferation. However, these findings are discrepant with observations showing no difference in the proliferation rate of ERK1-deficient embryonic fibroblasts (Pages et al, 1999) whereas RNAi silencing of ERK1 inhibited the proliferation of HeLa cells to the same extent as ERK2 silencing (Liu et al, 2004). Recent studies emphasize this controversy (Sanjo et al, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…In FT210 cells, ERK1 depletion caused cell-cycle arrest at G 2 , whereas the loss of ERK2 induced arrest at G 1 (Liu et al, 2004). In NIH 3T3, knockdown of ERK2 almost completely abolished normal and Ras-dependent cell proliferation.…”
Section: Introductionmentioning
confidence: 94%
“…Activation is independent of extracellular growth factor input (Dangi and Shapiro, 2005), and inhibition causes spindle defects (Horne and Guadagno, 2003). Additionally, interfering with MEK1 signaling via expression of dominant-negative mutants, use of chemical inhibitors, or RNA interference (RNAi) significantly delays mitotic entry (Wright et al, 1999;Roberts et al, 2002;Liu et al, 2004), suggesting the existence of a novel mitotic target of MEKmediated signaling that promotes mitotic entry. Surprisingly, one apparent mitotic target of MEK1 is the mammalian Golgi apparatus (Acharya et al, 1998).…”
Section: Introductionmentioning
confidence: 99%